Wewenang Hakim Melakukan Pembatalan Pada Akta Notaris Sebagai Alat Bukti Dalam Persidangan - Ramdlon Mahuraden Tuakia (Kyadiren, 2022)
The study is aimed at examining the purpose of the judge in canceling the notarial deed at the trial where the deed becomes evidence. The external, formal and material power adheres to the deed as a proof. The strength of the deed under hand has no legal force. Interested parties can apply for cancellation if they do not want the deed from a notary through filing a lawsuit. Notaries who do not comply and commit violations in making the deed will be dealt with in accordance with the applicable code of ethics and may be subject to dismissal.